THE ANALYZE OF INFLUENCE MOTIVATION AND WORK SATISFACTION TO EMPLOYEES PERFORMANCE OF PT INDOTECH METAL NUSANTARA KARAWANG - Neneng Sofiyanti; Dian Hakip Nurdiansyah; Anggi Pasca Arnu (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2019)
The result of preliminary studies was found that Employees Performance is not optimal. Motivation and work satisfactin is the most dominant factor of influence. The research of target is obtaining empiric evidence and finding clarity of phenomenon and also conclusion about the influence of motivation and work satisfaction to employees performance PT Indotech Metal Nusantara Karawang. Expected can giving something for development economic science especially; management development of institute, public service management, marketing management, human resource and generally of economic science. The method used is descriptive survey and explanatory survey. The sampling technique was used simple random sampling. Data analysis techniques is to expose each variable we,it used range scale. Data analysis technique used correlation analysis technique variables and Path Analysis Technique, to expose the influence of motivation and work satisfaction. The conclusion from the examination that Motivation at PT Indotech Metal Nusantara Karawang is good with total score 628,6. Work satisfaction at PT Indotech Metal Nusantara Karawang is good with total score 613,9. Employees performance at PT Indotech Metal Nusantara Karawang is good with total score 626,7. Influence directly motivation to employees performance of 31,25%, while the indirect influence of 3,06%. In total influences of motivation to employees performance at PT Indotech Metal Nusantara Karawang of 34,31%. Influence directly work satisfaction to employees performance of 7,13%, while the indirect influence of 3,06%. In total influences of motivation to employees performance at PT Indotech Metal Nusantara Karawang of 10,19%. Simultaneously influence motivation end work satisfaction to employees performance at PT Indotech Metal Nusantara Karawang of 44,50%.